2010
DOI: 10.1073/pnas.0911446107
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal cancer-related gene 4 is a secreted inducer of cell senescence expressed by aged CNS precursor cells

Abstract: Mammalian aging is thought to be partially caused by the diminished capacity of stem/precursor cells to undergo self-renewing divisions. Although many cell-cycle regulators are involved in this process, it is unknown to what extent cell senescence, first identified as irreversible growth arrest in vitro, contributes to the aging process. Here, using a serum-induced mouse oligodendrocyte precursor cell (mOPC) senescence model, we identified esophageal cancer-related gene 4 (Ecrg4) as a senescence inducer with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 40 publications
5
76
0
Order By: Relevance
“…Cell cycle analysis was performed by flow cytometry, and the result suggested that rhC2ORF40 could arrest the ESCC cells at the G 1 /S checkpoint and delay the transition of the cell cycle into the S phase (Table I), which was consistent with our previous C2ORF40 gene transfection result (4). Consequently, rhC2ORF40 protein slowed down cell cycle progression, and caused cell cycle G 1 phase block.…”
Section: Production Of Purified Rhc2orf40 Proteinsupporting
confidence: 77%
“…Cell cycle analysis was performed by flow cytometry, and the result suggested that rhC2ORF40 could arrest the ESCC cells at the G 1 /S checkpoint and delay the transition of the cell cycle into the S phase (Table I), which was consistent with our previous C2ORF40 gene transfection result (4). Consequently, rhC2ORF40 protein slowed down cell cycle progression, and caused cell cycle G 1 phase block.…”
Section: Production Of Purified Rhc2orf40 Proteinsupporting
confidence: 77%
“…Cellular senescence can inhibit tumor formation by modulating the redox state in CSCs and by regulating p27 in glioma cells (26,27). In addition, GICs derived from wild-type mice expressing the senescence-promoting factor esophageal cancer-related gene 4 (Ecrg4) caused significantly reduced tumor formation in mouse brains compared with cells from Ecrg4-knockdown mice (28). We observed that miR340 overexpression in hGICs decreased DNA methyltransferase 1 (DNMT1) expression ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Fourth, additional work is needed to validate more genes found on the array and examine their role in mediating some of the developmental effects of BDS. For example, three of the five most highly regulated genes found on the array are genes that regulate neural stem cell proliferation and survival (eg, ECRG, Kujuro et al, 2010;ENPP2, Koike et al, 2011;SOSTDC1, Lintern et al, 2009), providing a possible molecular explanation for the reduced DNA content seen in the hippocampus of pups exposed to BDS (Wei et al, 2010). Finally, our data does not allow us to assess the exact contribution that a decrease in LBP expression in the hippocampus has in the behavioral sequelae of animals exposed to BDS, nor do we imply that all the behavioral consequences of BDS are mediated by its ability to inhibit expression of LBP.…”
Section: Study Limitationsmentioning
confidence: 99%